Exploring the Remote Reactivity of π-Extended Carbonyl Compounds: The Vinylogous Alkylidene Malononitrile Activation Strategy - Curti, Claudio; Sartori, Andrea; Battistini, Lucia; Zanardi, Franca (Synlett, 2018)
The installation of malononitrile into π-extended carbonyl compounds gives rise to vinylogous alkylidene malononitriles (also known as π-extended dicyanovinylidenes), the direct functionalization of which at remote C(sp3) pronucleophilic sites becomes possible and viable. Starting from easily accessible representative polyunsaturated malononitriles, mild conditions were found to directly couple them to complementary enal acceptors. In all cases, the malononitrile handle proved an indispensable (and optionally traceless) activating ingredient for the vinylogous reactions to proceed efficiently and selectively. Merging the vinylogy concept with the malononitrile HOMO-raising activation strategy and complementary organocatalytic activation modalities (i.e. LUMO-lowering iminium ion activation) turned out to be a successful option, as demonstrated by the number of diverse carbocyclic and heterocyclic chiral products that were (stereo)selectively accessed through this chemistry.1 Introduction2 Reactions of Cyclohexenylidene Malononitriles with Enals3 Reactions of Allylidene Malononitriles with Enals4 Reactions of Indolylmethylene Malononitriles with Enals5 Conclusion
Keywords: asymmetric synthesis; carbocycles; heterocycles; organocatalysis; remote functionalization; vinylogous malononitriles; vinylogy